2008
DOI: 10.1007/s00455-008-9164-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Due to Unilateral Infarction in the Vascular Territory of the Anterior Insula

Abstract: We describe a patient who suddenly developed dysphagia for liquids as the sole manifestation of stroke. Magnetic resonance imaging (MRI) revealed a right-sided infarction of the superior part of the anterior insula and a small portion of the adjacent medial frontal operculum. These findings confirm the role of the anterior insula as a critical area in humans with regard to the origin of dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 15 publications
0
27
0
2
Order By: Relevance
“…28,29 A recent intracortical microstimulation study found that stimulation of the anterior sector of the dorsal insula triggered swallowing, mouthing, and chewing in monkeys. 30 Oroalimentary behavior, including motor automatisms, has been described during epileptic seizures originating in this part of the insula.…”
Section: Neuroanatomical Predictors Of Acute Risk Of Aspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 A recent intracortical microstimulation study found that stimulation of the anterior sector of the dorsal insula triggered swallowing, mouthing, and chewing in monkeys. 30 Oroalimentary behavior, including motor automatisms, has been described during epileptic seizures originating in this part of the insula.…”
Section: Neuroanatomical Predictors Of Acute Risk Of Aspirationmentioning
confidence: 99%
“…31 Stroke patients with discrete lesions of the anterior insula have been shown to suffer from dysphagia in small case studies. 28,29 Furthermore, sensory and motor signaling from and to various areas might be mediated by the insula (eg, interacting with the oropharynx and the esophagus). 32 A magnetoencephalographic study demonstrated consistent long-lasting activation of the insular cortex before swallowing.…”
Section: Neuroanatomical Predictors Of Acute Risk Of Aspirationmentioning
confidence: 99%
“…First, several clinical and functional imaging data point at a contribution of intrasylvian cortex to swallowing. For example, an investigation of patients with unilateral damage to the insular cortex was able to document dysphagia in all three cases with infarction of the anterior insula, whereas a subject who had suffered ischemia of posterior intrasylvian cortex did not exhibit any swallowing problems (Daniels and Foundas 1997; for further evidence see Riecker et al 2009). And, second, several case studies noted the presence of bucco-facial apraxia in patients suffering from, by and large, circumscribed uni-or bilateral insular lesions (Habib et al 1995;Nagao et al 1999).…”
Section: Participation Of the Anterior Insula In The Control Of Non-smentioning
confidence: 99%
“…With respect to its cortical representation, the following representational sites have been described: bilateral inferior pre-and postcentral gyri (39,59), bilateral anterior insula (25,26,51), anterior cingulate cortex (59), bilateral temporal pole, and the supplementary motor area (SMA) (23,45). Opercular areas are lateralized to the left dominant hemisphere (40,41).…”
mentioning
confidence: 99%